Investigating the Effects of Smoking and Cognitive Load Differentiation on Prospective Memory Performance - Pakyürek, Gün; Şenyüz, Levent (Addicta: The Turkish Journal on Addictions, 2019)
Nicotine, the most harmful chemical found in cigarettes, is known to affect the cholinergic system and to alter cognitive processes such as attention and memory, especially sensory and motor activities; these effects vary depending on the level of cognitive load. Considering that smoking affects the brain structures associated with prospective memory, the effect on prospective memory performance is thought to possibly differ under different cognitive load conditions. Therefore, the main purpose of the present study is to compare the performance of participants in a time-based prospective-memory task under smoking and cognitive load conditions. When analyzing the data according to smoking condition, smokers are found to be quicker than non-smokers in terms of response time in the ongoing N-Back task. In addition, smokers have been found to make more prospective memory mistakes than non-smokers, especially under high cognitive load conditions. To